Some properties of Appell type degenerate Bell polynomials - Ozat, Zeynep; Ozarslan, Mehmet Ali; Cekim, Bayram (Hacettepe Univ, Fac Sci, 2025)
In recent years, the degenerate versions of some polynomial families such as Bernoulli, Euler, Apostol and Bell polynomials have been intensively studied in the literature. Many new forms of Bell polynomials such as degenerate, partially degenerate and fully degenerate have attracted attention. The specific aim of this paper is to introduce a new family of general degenerate Bell type polynomials with the help of degenerate App ell polynomials and explore their properties, including explicit form, determinant representation, recurrence relation, lowering and raising operators and difference equation. Then, after discussing the special cases of App ell type degenerate Bell polynomial families, new polynomial families including Bernoulli and Euler polynomials are given. Furthermore, corresponding results are obtained for these new families. Lastly, new relations and summation formulas are obtained including Stirling numbers and App ell type degenerate Bell polynomials. Finally, we establish theorems that provide various families of multilinear and multilateral generating functions for the App ell type degenerate Bell polynomials.
Keywords: Appell polynomials; Bell polynomials; degenerate Bell polynomials; Bell based Appell polynomials; Stirling numbers